ANALISIS RASIO PROFITABILITAS DAN SOLVABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - dinar, sundinar; Banjarnahor, Haposan (LPPM Universitas Putera Batam, 2022)
The stock price is an important value for the company where the higher the value of the stock can certainly produce positive things for the company, both material or profit and corporate image that can attract investors. This study aims to examine the effect of profitability and solvency ratios on stock prices in manufacturing companies listed on the Indonesia Stock Exchange. This study examines several manufacturing companies in the consumption industry sector that publish their financial statements for the period 2016 to 2020. There are several data analyzes used, namely classical assumption tests such as normality tests, multicollinearity tests, autocorrelation tests and heteroscedasticity tests. The results of the data normality test have a normal distribution of significance, namely 0.125, which is greater than 0.5, than the other classical assumption tests, there are no deviations. The results of multiple linear regression are ROE and DER have a positive influence on stock prices and on hypothesis testing, have a value of 17.542 and f-table 3.25 and a sig value of 0.000 <0.05, therefore ROE and DER have an effect on stock prices, then with ttest ROE has an effect on stock prices where the t-value is 0.002 <0.05 and DER has no effect on stock prices where the t-value is 0.131 > 0.05. The coefficient of determination of the value of R2 is 48%, therefore the ROE and DER variables affect the stock price by 48% and the remaining 52% is influenced by other variables or factors that are not included in this study.